Quality and Yield of Edible Vegetables from Landscape Design - Ana-Maria-Roxana Istrate; Mirela Cojocariu; Gabriel-Ciprian Teliban; Alexandru Cojocaru; Vasile Stoleru (Horticulturae, 2023)
This study evaluated the effects of raised beds on crop production and quality in home gardens. The crops were grown using optimal management techniques and crop rotation principles based on organic farming. Three experimental versions were compared: V1 with 40-centimetre-high raised beds, V2 with 20-centimetre-high raised beds, and V3 with ground-level beds as the control. The results showed consistent dry weight and moisture content across all three versions for most vegetable varieties. The sweet pepper ‘Barbara’ stood out significantly, as V3 had the highest dry weight percentage (10.28%) and V2 had the highest moisture content percentage (93.40%). Nutrient analysis revealed no significant differences in lipid, ash, protein, nitrogen, or caloric value among the different versions of most vegetables. However, version V3 of the tomato ‘Tigerella’ showed the highest crude fibre content. Variations were observed in lycopene, ß-carotene, and calcium content among different versions of specific vegetables. Anti-nutritive compounds and average yield varied among the experimental versions for certain plant species. These findings have implications for dietary choices and can guide sustainable food production. It is recommended to consider raised beds, particularly V3, for cultivating sweet pepper ‘Barbara’, and further research is encouraged to explore the potential health benefits of version V3 of tomato ‘Tigerella’. These insights provide valuable vegetable science and nutrition information and can guide agricultural practices.